Jinsei Annai, "life's guide" : glimpses of Japan through a popular advice column - McKinstry, John; McKinstry, Asako Nakajima (Armonk, New York : M.E. Sharpe, Inc., 1991)
A scholarly work that aims to be both broad enough in scope to satisfy upper-division undergraduates studying folk belief and narrative and detailed enough to meet the needs of graduate students in the field.
CHAPTER 1. Introduction : an advice column as a mirror of Japanese culture? -- CHAPTER 2. Mr. Wrong : complaints against husbands -- CHAPTER 3. Responses to Mr. Wrong -- CHAPTER 4. "I am bothered by relations with others" -- CHAPTER 5. Problems with in-laws -- CHAPTER 6. Additional sources of family tension -- CHAPTER 7. Courtship and affairs of the heart -- CHAPTER 8. Two secondary topics -- CHAPTER 9. Comments in summation.
Keywords: HISTORY -- ASIA JAPAN